THE VERSION REGARDING SPECIAL SERVICES OF THE ISLAMIC REPUBLIC OF IRAN FOR INVOLVEMENT IN THE DEATH OF THE SSNG K-141 "KURSK" IN THE CONTEXT OF MARITIME SAFETY, SECURITY AND DEFENCE OF THE WOLD ... - KALINICHENKO, Oleksandr; SIMONENKO, Olena (Zenodo, 2024)
The geopolitical evolution of Iran in the 21st century was considered. Versionsregarding the death of the "Kursk" APRK are listed. Attention is focused on the controversy of thePacific submariners, who in one way or another are involved in the analyzed character: ValeryRyazantsev - my first chief officer of the SSN K-45 and Maksym Klimov - the commander of themine-torpedo combat department of the third generation Pacific nuclear submarines of projects 971and 949A. Attention was drawn to the aspects and motives of the interested parties regarding thetransfer of cavitating torpedoes, as well as to the cross-species and international composition of theparticipants in the military exercises in the waters of the Barents Sea, the management of whichclearly went beyond the powers of the Commander of the Northern Fleet of the Russian Navy. Thefacts on which the author of the version relied were given. Chronological, comparative, problemmethods of historical scientific research and the method of content analysis are ...